Constraints on the K0S →μ+μ− branching fraction - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; et al. (Physical review letters, 2020)
A search for the decay K0S→μ+μ− is performed using proton-proton collision data, corresponding to an integrated luminosity of 5.6 fb−1 and collected with the LHCb experiment during 2016, 2017, and 2018 at a center-of-mass energy of 13 TeV. The observed signal yield is consistent with zero, yielding an upper limit of B(K0S→μ+μ−)<2.2×10−10 at 90% C.L.. The limit reduces to B(K0S→μ+μ−)<2.1×10−10 at 90% C.L. once combined with the result from data taken in 2011 and 2012.
Im Titel sind "0", "+", "-" hochgestellt, "S" ist tiefgestellt
R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, J.T. Borsuk, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, L. Witola, A. Zhelezov [und weitere] (LHCb Collaboration)
Gesehen am 01.02.2021